PENGARUH STRUKTUR MODAL DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN KELUARGA - Robith Hudaya (Jurnal Riset Akuntansi, 2017)
The objective of this research was to search and analyze whether Capital Structure and Intellectual Capital has influence on Financial Performance of Family Company proxyfied with Return on Equity (ROE) and Tobins’Q. By using manufacturing family company sample that listed in Indonesia Stock Exchange during 2014-2016, the study found that that Capital structure has influence on Financial Performance as proxified with return on equity. The study also found that, Intellectual Capital has influence on Financial Performance as proxified with Tobins’Q.